ORNİTHOGALUM OLİGOPHYLLUM E. D. CLARKE VE ORNİTHOGALUM ORTHOPHYLLUM TEN. KARYOLOJİK YÖNDEN İNCELENMESİ - ÖGER, SİBEL (Fırat Üniveristesi, 2021)
Bu çalışmada, Asparagaceae familyasının önemli cinslerinden biri olan Ornithogalum cinsine ait iki tür (Ornithogalum oligophyllum E. D. Clarke ve Ornithogalum ortophyllum Ten.) karyolojik yönden incelenmiştir. Sitotaksonomik çalışmalar için toplanan örneklerin soğanlarından yararlanılmıştır. Bölünür somatik hücrelerde yapılan çalışmalar sonucunda, türlerin kromozom sayımları ve karyotip analizleri yapılarak idiyogramları çizilmiştir. Kromozom sayıları Ornithogalum oligophyllum türünde 2n=20 ve Ornithogalum orthophyllum türünde 2n=14 olduğu tespit edilmiştir.

In this study, two species of Ornithogalum L. genus (Ornithogalum oligophyllum E. D. Clarke and Ornithogalum orthophyllum Ten.), one of the important genus of the Asparagaceae family, were examined in terms of karyological aspects. For cytotaxonomic studies, corms of the collected samples were used. As a result of the studies carried out on dividing somatic cells, idiograms were drawn by counting the number of chromosomes and conducting karyotype analyzes of the species. The chromosome numbers were found to be 2n=20 for the Ornithogalum oligophyllum species and 2n=14 for the Ornithogalum orthophyllum species.
Karyological examination of Ornithogalum oligophyllum E. D. Clarke and Ornithogalum orthophyllum Ten.
Keywords: Biyoloji